Sulfated Alkyl Glucopyranans with Potent Antiviral Activity Synthesized by Ring-Opening Copolymerization of Anhydroglucose and Alkyl Anhydroglucose Monomers - Shiming Bai; Davaanyam Budragchaa; Shuqin Han; Taisei Kanamoto; Hideki Nakashima; Takashi Yoshida (International Journal of Polymer Science)
Sulfated glucopyranans having long alkyl groups were prepared by the ring-opening copolymerization of benzylated 1,6-anhydroglucopyranose with 3-O-octadecyl 1,6-anhydro-β-d-glucopyranose monomers, and subsequent deprotection and sulfation. Water-soluble sulfated glucopyranans with 2.8 and 4.7 mol% of 3-O-octadecyl group and lower molecular weights of M-n = 2.5 × 103–5.1 × 103 have potent anti-HIV activity at 0.05–1.25 μg/mL, even though sulfated polysaccharides with molecular weights below M-n = 6 × 103 had low anti-HIV activity. The interaction with poly-l-lysine as a model compound of proteins was analyzed by SPR, DSL, and zeta potential, indicating that the sulfated 3-O-octadecyl glucopyranans had high association and low dissociation rate constants, and the particle size increased after addition of poly-l-lysine. The anti-HIV activity was induced by electrostatic interaction between sulfate groups and amino groups of poly-l-lysine and by the synergistic effect of the hydrophobic long alkyl chain and hydrophilic sulfated group.